2021
DOI: 10.1108/cfri-03-2021-0052
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficiency financing and the role of green bond: policies for post-Covid period

Abstract: PurposeOne of the major negative effects of the Coronavirus outbreak worldwide has been reduced investment in green energy projects and energy efficiency. The main purpose of this paper is to study the role of green bond proposed by the World Bank in 2008, as a reliable instrument to enhance the capital flow in energy efficiency financing and to develop green energy resources during and post the current challenging global time.Design/methodology/approachWe model energy efficiency for 37 members of OECD through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 78 publications
2
9
0
Order By: Relevance
“…Based on our analysis, a negative association between GBs and ENI exists in the majority of the EU nations. This finding is consistent with prior empirical research such as the studies by Azhgaliyeva et al [12] and Tu and Rasoulinezhad, [26] who confirm the negative impact of GBs on ENI. Our results are partly consistent with those of Azhgaliyeva et al [12] for ASEAN nations, or with those by Zhang et al [23] for China, and Geddes et al [32] for Australia, UK, and Germany, all of which showed that GBs improve ENE.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Based on our analysis, a negative association between GBs and ENI exists in the majority of the EU nations. This finding is consistent with prior empirical research such as the studies by Azhgaliyeva et al [12] and Tu and Rasoulinezhad, [26] who confirm the negative impact of GBs on ENI. Our results are partly consistent with those of Azhgaliyeva et al [12] for ASEAN nations, or with those by Zhang et al [23] for China, and Geddes et al [32] for Australia, UK, and Germany, all of which showed that GBs improve ENE.…”
Section: Discussionsupporting
confidence: 92%
“…The nonparametric quantile regression described below in its initial basic form was used, which was asserted by empirical studies of Azhgaliyeva et al [12] and Tu et al [26] ENI t = 𝛼 𝜃 (GBs t ) + 𝜇 𝜃 t (4) where ENI t and GBs t display energy intensity and green bonds, respectively, throughout time t. 𝜃 shows the 𝜃th quantile of GBs. These was no prior information of the GBs-ENI nexus, therefore the factor load 𝛼 𝜃 ((GBs t )) was not known.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inflation rate is a financial factor that influences the green market expansion, a higher level of inflation negatively affects the investor's decisions (Anh Tu et al 2020). In addition, analyzing the OECD members Tu and Rasoulinezhad (2021) find that inflation has a negative and significant impact on energy efficiency. Therefore, investors consider inflation when they decided to finance energy efficiency projects.…”
Section: Data Descriptionmentioning
confidence: 99%
“…However, the consumption of NRE is a threat to environmental deterioration, being the major contributor to carbon dioxide (CO2) emission, and has become a global concern (Cevik et al, 2021;Tu and Rasoulinezhad, 2021). Hence, countries are increasingly focusing on renewable energy (RE) sources to tackle climate change, which is further triggered by the concern over the limited supply of NRE and the ambition to achieve sustainable development goals (SDGs) (Amri, 2017;Wang et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%